2452. Treatment and Outcomes of Daptomycin-Nonsusceptible Methicillin-Resistant Staphylococcus aureus Bloodstream Infections. (26th November 2018) - Hadid, Hind; Bardossy, Ana Cecilia; Misikir, Helina; Perri, Mary Beth; Zervos, Marcus; Herc, Erica
Abstract: Background: Daptomycin (dap) is approved as an alternative to vancomycin (van) for therapy of methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infection (BSI). Cases of therapy failure associated with the emergence of daptomycin-nonsusceptible (DNS) MRSA strains have been documented. Information on the treatment and outcome of DNS MRSA BSI is scarce. This study describes the treatment and outcome of patients with DNS MRSA BSI at our healthcare center. Methods: This is a retrospective review of patients with DNS (E-test MIC >1.0 µg/mL) MRSA BSI at a tertiary healthcare center in Detroit, Michigan between September 24, 2005 and March 31, 2018. The variables collected were: BSI source, inpatient and discharge antibiotic therapy, BSI duration, in-hospital and 90-day mortality, and 90-day MRSA BSI recurrence. Inpatient therapy was defined as the treatment used for the most consecutive days from index DNS MRSA blood culture during hospitalization. Discharge therapy is the treatment used post-discharge or on the expiration date. Antibiotics used for ≤2 days were excluded. Results: A total of 32 nonduplicate patients with DNS MRSA BSI were identified. One patient with an inaccessible chart was excluded. The source of BSI was endovascular in 9 (29%) patients, secondary BSI in 14 (45%), central-line associated in 3 (10%), and unknown in 5 (16%). A total of 24 different antibiotic regimens were used to treat DNS MRSA BSI. Van monotherapy was the most commonly used regimen for inpatient and discharge therapy, followed by dap + ceftaroline (cef). Table 1 is a summary of the results. Conclusion: A variety of therapeutic regimens was used to treat DNS MRSA BSI in our cohort. However, van monotherapy was the most common inpatient and discharge regimen. Disclosures: All authors: No reported disclosures.